The collected works (gsuṅ ʼbum) of the incomparable Lord Tsoṅ-kha-pa Blo-bzaṅ-grags-pa - Tsoṅ-kha-pa Blo-bzaṅ-grags-pa, 1357-1419 (Rje yab sras gsum gyi gsuṅ ʼbum, 1978)
Writings on Buddhist philosophy and practice by the founder of the Gelukpa tradition of Tibetan Lamaism.